‏‎2023 ‎إلى ‏‎2014 من ‎ CAAT تطور تأمين نقل السلع في الجزائر ‏ دراسة حالة الشركة الجزائرية للتأمين ‏ - رشيد بوخزنة; قديري الهاشمي; سعدين محمد (جامعة الوادي University of Eloued, 2025)
"‏ تهدف الدراسة الى وصف وتقييم تأمين نقل السلع في الجزائر، من خلال استعراض الاطار ‏القانوني والتنظيمي لسوق التأمين الجزائري خلال الفترة 5014-2022، وتقييم الممارسات التقنية ‏لتأمين نقل السلع في الشركة الجزائرية للتأمين ‏CAAT‏ وتطور الاكتتاب والتعويضات في هذا الفرع ‏خلال الفترة 2017-2023 كدراسة حالة.‏ ‏ خلصت الدراسة الى ان سوق التأمين الجزائري شهد تحسنا من حيث الاطار التشريعي والتنظيمي ‏والمؤسساتي، الا ان تأمين نقل السلع لم يرقى الى مستوى تطور سوق التأمين The study aims to describe and evaluate good transport insurance in Algeria, by ‎reviewing the legal and regulatory framework of the Algerian insurance market during the ‎period 2014-2022, and evaluating the technical practices of good transport insurance at the ‎Algerian Insurance Company (CAAT), as well as the development of underwriting and ‎compensation in this sector during the period 2017-2023, as a case study.‎ ‎ The study concludes that the Algerian insurance market has witnessed improvements ‎in terms of the legislative, regulatory, and institutional framework, but good transport ‎insurance has not yet reached the level of development of the insurance market.‎
ماستر العلوم التجارية
Keywords: التأمين; تأمين نقل السلع; الشركة الجزائرية للتأمين ‏CAAT; Insurance; Goods Transport Insurance; Algerian Insurance Company CAAT